SISTEM INFOMASI PELELANGAN BARANG SECARA ONLINE PADA PT. PEGADAIAN (PERSERO) UNIT PELAYANAN CABANG PASAR 26 ILIR PALEMBANG - Arinda Lestari; John Roni Coyanda; Dasrial Dasrial (UNIVERSITAS INDO GLOBAL MANDIRI)
The information is very needed in the times. Where with the development of information technology in various develop a computerized system for generating an appropriate decision in achieving its objectives. Problems that will be discussed is how to design susatu information systems for data processing auction process more effective and efficient. The method can solve the above problems is a method of analysis of the approach to the object and approach the data flow, the analysis that is in use is to create a data flow diagram (DAD), flowcharts, data dictionary, Entity Relationship Data (ERD), the chart is structured, normalization, specification process. In building this system juag authors use the programming language PHP and MySQL for the process of updating the data in the database, is helpful in managing the auction data and order management process of auction items can be done quickly and accurately so that remind effectiveness and efficiency